890The prevalence and risk factors for Coxiella burnetii on commercial dairy goat farms in Australia. (2nd September 2021) - Hou, Kangwei; Firestone, Simon; Wiethoelter, Anke; Stenos, John; Lignereux, Louis; Clark, Nicolas; Aleri, Joshua; Magalhães, Ricardo; Stevenson, Mark
Abstract: Background: Despite the potentially important role that intensively managed dairy goats play in the spread of Q fever, the prevalence of Coxiella burnetii among dairy goat herds in Australia is largely unknown. The aim of this cross-sectional study was to estimate the prevalence of coxiellosis-positive dairy goat herds in Australia and to identify risk factors associated with coxiellosis positivity. Methods: Owners or managers of commercial dairy goat herds were contacted and asked to complete a questionnaire about risk factors for coxiellosis and to provide a bulk tank milk (BTM) sample. BTM samples were tested using an enzyme-linked immunosorbent assay (ELISA) and real-time quantitative polymerase chain reaction (RT-PCR) targeting the Com1 and IS 1111 sections of the C. burnetii genome. Questionnaire responses from coxiellosis positive and coxiellosis negative herds were compared using frequency cross-tabulations and multivariable logistic regression. Results: Herd managers from 49 of the 61 commercial dairy goat herds in Australia took part in the study. Of this group, three BTM samples were found to be both ELISA and RT-PCR positive. Two BTM samples were ELISA positive but RT-PCR negative. There were 10 (95% CI 4.4 to 22) C. burnetii positive herds per 100 herds at risk. Conclusions: The prevalence of coxiellosis among commercial dairy goat farms in Australia is relatively low. Key messages: The Australian dairy goat industry should focus on biosecurity measures and risk management plans to reduce the probability of C. burnetii introduction.